Persuasive Language in Cicero A close reading and commentary - Fotheringham, Lynn S. (Bulletin of the Institute of Classical Studies Supplements, 2013)
This innovative approach to Cicero's persuasive language analyses the style and structure of one of his important speeches in more detail than has ever been done before. It applies ideas from modern linguistics (sentential topic, lexical patterning, interactional discourse), and explores the possibilities and limitations of quantitative analysis, made easier by modern computing power, in the areas of syntax and vocabulary. The result is a reading of the Pro Milone as a unified text, whether aimed at persuading the jury to acquit Milo or at persuading a wider audience that Milo should have been acquitted. This reading not only contributes to our understanding of late republican discourse, but also suggests a new methodology for using the study of language and style to illuminate literary/historical aspects of texts.